Case Report: Intercostal Lymph Node Metastasis: A Case Report and Review of the Literature - Zhou, Yurong; Hou, Jinxuan; Meng, Ning; Daniel, Staiculescu; Chen, Jiang; Xu, Liying (Frontiers in Oncology, 2021)
The axillary lymph nodes are the primary group responsible for lymphatic drainage in the breast and, consequently, are the most common location for breast cancer metastasis. However, lymphatic pathways running from the breast, via intercostal spaces, to parasternal lymph vessels have also been identified. According to the American Joint Committee on Cancer eighth edition manual, regional lymph node metastasis normally travels to the ipsilateral axillary, supraclavicular, subclavicular, and internal mammary lymph nodes. The presence of intercostal metastasis is out the range of these regional lymph nodes. It is very rare for intercostal lymph nodes to be the extra-axillary site of metastasis in breast cancer, and it has been little reported on in the literature. Despite its rarity, it has the capacity to adversely affect the prognosis of breast cancer and drastically influence treatment choice. Here, we analyze such a case, with a patient receiving a radical mastectomy and metastatic intercostal lymph node dissection due to the presence of intercostal lymph node metastasis indicated via MRI. Furthermore, the potential application of preoperative 3-dimensional (3D) visualization and surgical planning is also discussed.